الآثار الاقتصادية والاجتماعية لجائحة كورونا (كوفيد- 19 المستجد) محليا، عربيا وعالميا - سلاطنية, إبتسام; غياط, شريف (جامعة الوادي - University of Eloued, 2022)
هدف هذه الدراسة إلى محاولة تسليط الضوء على التداعيات الاقتصادية والاجتماعية لفيروس كورونا (كوفيد 19 المستجد) على دول العالم عامة، ودول المنطقة العربية خاصة، حيث سيتم تقديم لمحة مختصرة عن ماهية جائحة كورونا وكيفية انتقالها مع استعراض جملة من البيانات والاحصائيات التي توضح عدد الإصابات والوفيات بهذه الجائحة، وتوضيح تداعياتها الاقتصادية والاجتماعية عالميا وعربيا. ليتم بعد ذلك سرد السياسات والإجراءات الاحترازية المتخذة للتصدي لفيروس كورونا المستجد. وقد توصلت الدراسة إلى أنّ تداعيات أزمة فيروس كورونا التي تزامنت مع أزمة انهيار أسعار البترول، وكانت بذلك صدمة مزدوجة على اقتصاديات دول العالم وخاصة الدول العربية منها، من أسوأ الأزمات وأشدها تأثيراً خلال القرن الحادي والعشرين، فقد كان لها آثار كارثية شملت مختلف النواحي الاقتصادية، المالية والاجتماعية، إضافةً إلى الخسائر البشرية الكبيرة وإجبار نصف سكان الكرة الأرضية على ملازمة منازلهم دون القيام بأي عمل This study aims to try to shed light on the economic and social repercussions of the Corona virus (Covid 19 emerging) on the countries of the world in general, and the countries of the Arab region in particular. A brief overview of the Corona pandemic and how it is transmitted will be provided. With a review of a number of data and statistics that show the number of injuries and deaths in this pandemic, and clarifying its economic and social repercussions globally and in the Arab world. The policies and precautionary measures taken to contain this virus will then be listed. The study concluded that the repercussions of the Corona virus crisis, which coincided with the crisis of the collapse of oil prices, and thus was a double shock to the economies of the countries of the world, especially the Arab countries, is one of the worst and most influential crises during the twenty-first century, as it had catastrophic effects that included various economic aspects, Financial and social, in addition to the great human losses and forcing half of the world's population to stay in their homes without doing any work.
The Economic and Social effects of The Corona Pandemic (Covid-19) Locally, Arab And Global
مقال
Keywords: فيروس كورونا؛ مرض كوفيد- 19 المستجد؛ الاقتصاد العالمي؛ اقتصاديات الدول العربية؛ التداعيات الاقتصادية والاجتماعية.; Coronavirus; The emerging Covid-19 disease; International Economy; The economies of the Arab countries; Economic and social repercussions.